Organometallic Halide Perovskite Synthesis in Polymer Melt for Improved Stability in High Humidity. Issue 47 (20th May 2016) - Murphy, John P.; Andriolo, Jessica M.; Ross, Brandon M.; Wyss, Gary F.; Zander, Nicole E.; Skinner, Jack L.
ABSTRACT: A new organometallic halide perovskite (OHP) synthesis method, whereby a polymer melt is used to thermodynamically drive the reaction that forms OHP crystallites, is demonstrated. The synthesis method allows for the facile encapsulation of moisture-sensitive OHP without the loss of simplicity during fabrication, which makes OHP materials so attractive for the photovoltaic industry. Degradation of OHP crystallites embedded in a polystyrene matrix was studied using UV-Vis absorbance over a period of several days. The OHP crystallites degrade as a result of the reversible nature of the reaction that forms the crystallites. After the reversion to precursors (PbI2 and CH3 NH3 I) the CH3 NH3 I irreversibly degrades [2] allowing the degradation to be tracked via optical interrogation. Additionally, surface morphology and elemental analysis of fabricated samples was carried out using SEM/EDS techniques.